Tim-3 protects against cisplatin nephrotoxicity by inhibiting NF-κB-mediated inflammation - Peiyao Li; Xuemiao Li; Wenbin Wu; Mengjia Hou; Guanyi Yin; Zhonghang Wang; Ziyu Du; Yuanfang Ma; Qiang Lou; Yinxiang Wei (Cell Death Discovery, 2023)
Abstract The impact of Tim-3 (T cell immunoglobulin and mucin domain-containing protein 3) on cisplatin-induced acute kidney injury was investigated in this study. Cisplatin-induced Tim-3 expression in mice kidney tissues and proximal tubule-derived BUMPT cells in a time-dependent manner. Compared with wild-type mice, Tim-3 knockout mice have higher levels of serum creatinine and urea nitrogen, enhanced TUNEL staining signals, more severe 8-OHdG (8-hydroxy-2’ -deoxyguanosine) accumulation, and increased cleavage of caspase 3. The purified soluble Tim-3 (sTim-3) protein was used to intervene in cisplatin-stimulated BUMPT cells by competitively binding to the Tim-3 ligand. sTim-3 obviously increased the cisplatin-induced cell apoptosis. Under cisplatin treatment conditions, Tim-3 knockout or sTim-3 promoted the expression of TNF-α (tumor necrosis factor-alpha) and IL-1β (Interleukin-1 beta) and inhibited the expression of IL-10 (interleukin-10). NF-κB (nuclear factor kappa light chain enhancer of activated B cells) P65 inhibitor PDTC or TPCA1 lowed the increased levels of creatinine and BUN (blood urea nitrogen) in cisplatin-treated Tim-3 knockout mice serum and the increased cleavage of caspase 3 in sTim-3 and cisplatin-treated BUMPT cells. Moreover, sTim-3 enhanced mitochondrial oxidative stress in cisplatin-induced BUMPT cells, which can be mitigated by PDTC. These data indicate that Tim-3 may protect against renal injury by inhibiting NF-κB-mediated inflammation and oxidative stress.